An integration of µXRF and X-ray microdensitometry records in dendrochronology - Helama, Samuli; Saarinen, Timo; Suominen, Tapio; Fuentes, Mauricio; Frank, Thomas; Gunnarson, Björn (Elsevier, 2025)
X-ray based microdensitometry is conventionally used to produce climate-related tree-ring records. Micro X-ray fluorescence (µXRF) applications represent another growing area of interest and opportunities in dendrochronology. This paper demonstrates a method to correctly juxtapose and precisely synchronise the densitometry and µXRF profiles. Among µXRF variables, full fluorescence spectrum (FFS) corresponds distinctly well with the microdensitometry-based wood density variations. Accordingly, the FFS provides the most applicable variable to synchronise the µXRF and density profiles. The method proposed here can be used to demonstrate the strength and sign of µXRF variables and wood density relations. Moreover, the µXRF based records can be readily compared to density variables, such as the latewood maximum density, which is demonstrated in this paper.